(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the analgesic efficacy during labor between continuous epidural infusion and programmed intermittent epidural bolus using a combination of Anaropin 0.1% and Fentanyl 1 µg/ml. Method: A randomized controlled clinical trial was conducted on 80 parturients receiving epidural labor analgesia at the National Hospital of Obstetrics and Gynecology from August 2024 to June 2025. Forty women received continuous epidural infusion (CEI group), and forty received programmed intermittent epidural bolus (PIEB group), both using Anaropin 0.1% combined with Fentanyl 1 µg/ml. Results: The mean onset time of analgesia did not differ significantly (CEI group 10.70 ± 1.92 min; PIEB groups 10.88 ± 2.94 min; p > 0.05). After epidural administration, VAS scores decreased in both groups, but from the 20th minute onward, PIEB group achieved significantly better analgesia (p < 0.05). During the second stage of labor and episiotomy repair, VAS scores were significantly lower in PIEB group (p < 0.05). Both groups maintained good bearing-down sensation and pushing ability (p > 0.05). The mean total dose of local anesthetic was lower in PIEB group (29.90 ± 10.11 mg) than CEI group (38.06 ± 18.09 mg; p < 0.05). No patients in PIEB group required additional bolus doses (0% vs. 17.5%; p < 0.05). The duration of analgesia after delivery was longer in PIEB group (1.84 ± 0.24 h vs. 1.69 ± 0.37 h; p < 0.05). Maternal satisfaction was higher in PIEB group (100% vs. 92.5%). Conclusion: The programmed intermittent epidural bolus technique provided more effective and longer-lasting analgesia, required a lower total anesthetic dose, and achieved higher maternal satisfaction compared with continuous epidural infusion. Both techniques preserved bearing-down sensation and pushing ability, with no adverse effects on labor progression or cesarean section rates.